Minimum consumer budget: legal definition - Pyroha, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The work analyzes the disadvantages of normative and normative and statistical methods for determining the subsistence minimum. It is substantiated that they are not suitable for practical calculations due to the lack of objective criteria for setting standards for consumption of non-food products and services. The normative method of determining the subsistence minimum based on objective norms of consumption of food products and communal services is proposed.